Nonsurgical management of strip perforation using platelet-rich fibrin and MTA by matrix concept - A case report with one year follow-up - Kavalipurapu Venkata Teja; Sindhu Ramesh (Wolters Kluwer Medknow Publications, 2021)
Iatrogenic errors happen especially during endodontic treatment even with the experienced clinicians. It is impossible to predict the occurrence of an event. Although many of them can be corrected and managed successfully, few conditions might have the worst prognosis leading to uneventful extraction. The present case report highlights a 1-year follow-up of managed strip perforation in mesial canals of mandibular first molar, nonsurgically using MTA obturation. The present challenging case gives an insight on the importance of regenerative capacity and osteogenic potentiality of bioactive materials, when appropriate tissue engineering concepts are applied.